Membangun Moderasi Beragama: - Mustaqim Pabbajah; Ratri Nurina Widyanti; Widi Fajar Widyatmoko (IAI Darussalam, 2021)
The ratification of job creation law or omnibus law that changes clauses and establishes new regulations in a legal codification format has led to rejection in several regions in Indonesia because justice is not been reflected in terms of licensing aspects and weakened responsibilities. The omnibus law legislative process, which has so much been able to be completed in a short time, during the Covid-19 situation. This matter triggers the question of how the omnibus law legalization process is carried out based on the perspective of siyasah dusturiyah so how to analyze environmental content on environmental fiqh. This research is library research based on a normative approach by qualitative analysis methods. The theory used in this study is the theory of siyasah dusturiyah and environmental fiqh. The results of this study indicate that the omnibus law legislative process is not in line with the expectations of the benefit of dharuriyah, justice, and a sense of responsibility. The environmental content in the omnibus law does not yet represent environmentally friendly development so its management must be based on the principle of balance between utilization and environmental conservation.